The GASING Concrete-Abstract-Mental Computation Sequence: Learning Outcomes and Arithmetic Fluency in Elementary Mathematics - Jonatan Hasudungan Sihombing; Mubiar Agustin; Idat Muqodas; Jonatan Hasudungan Sihombing; Mubiar Agustin (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Mastery of basic arithmetic operations is foundational to elementary mathematics education, yet many students continue to struggle with both conceptual understanding and computational fluency. This study examined the effectiveness of the GASING method (Gampang, Asyik, dan Menyenangkan or Easy, Fun, and Enjoyable) in improving learning outcomes and arithmetic fluency among fourth-grade students in South Minahasa Regency, North Sulawesi, Indonesia. GASING employs a concrete-to-abstract-to-mental computation sequence built around critical points, integrating songs and games to promote engagement and automatization. A one-group pretest-posttest design was used, involving 64 students from 32 elementary schools who participated in a 15-day instructional program (November 25 to December 11, 2025) covering addition, multiplication, subtraction, and division. Overall mean scores improved significantly from 16.25 to 80.55 (N-Gain = 0.77, high category), with the Wilcoxon Signed-Rank Test confirming statistical significance (Z = −6.964, p < 0.001); all 64 students demonstrated improvement without exception. Division recorded the largest absolute gain (+66.87%) despite having the lowest baseline score, while computation speed converged to 1.12–1.29 minutes per item across all four operations, indicating a transition from procedural computation toward direct fact retrieval. These findings suggest that the GASING method was associated with substantial improvement in both conceptual mastery and arithmetic fluency simultaneously across all four basic arithmetic operations, supporting its potential as an evidence-based instructional approach for early mathematics education.